Detection of antimicrobial resistance in Glaesserella parasuis in South China using whole-genome sequencing - Ge, Qianwen; Fang, Liangxing; Yu, Yang; Sun, Ruanyang; Liao, Xiaoping; Zhang, Peng (Frontiers in Microbiology, 2025)
IntroductionGlaesserella parasuis causes Glässer’s disease in pigs, a leading cause of death in swine herds and a major contributor to economic losses in the global swine industry. Although several studies have investigated antimicrobial resistance in G. parasuis, the correlation between phenotypic and genotypic resistance remains unclear due to incomplete genetic resistance mechanisms detection.MethodsThe susceptibility of 117 clinical G. parasuis isolates to 7 antimicrobials was determined using a broth microdilution method. The sequences of 48 resistant isolates were obtained by whole-genome sequencing. Resistance genes, mutations, and group 1 vtaAs were detected based on whole-genome sequence data. Sequence types (STs) were identified by multilocus sequence typing (MLST).ResultsPhenotypic analysis showed that most isolates were susceptible to the tested antibiotics; resistance was most common against tetracycline (27%) and enrofloxacin (20%). All isolates were susceptible to ceftiofur. Analysis of whole-genome sequences revealed that resistance to tetracycline, amoxicillin, erythromycin, florfenicol, and chloramphenicol was frequently associated with the resistance genes tet(B) or tet(H), blaROB–1, erm(T), floR, and catA3, and enrofloxacin resistance was associated with mutations in GyrA, ParC, and ParE. MLST identified 25 STs, of which, 14 were novel. The sequenced strains were divided into two primary lineages, LI and LII. Group 1 vtaA genes were detected in 87.5% (n = 42) of the isolates.ConclusionThis study provides comprehensive insights into the molecular mechanisms responsible for drug resistance in G. parasuis, the characteristics of molecular epidemiology, and the virulence of resistant groups. Our findings can aid in the development of G. parasuis-specific clinical breakpoints and inform strategies for managing antimicrobial resistance in swine herds.